On the genealogy of strategies: resilience in the revolution. Issue 1 (2nd January 2017) - Michelsen, Nicholas
Abstract: This article examines what it means to write a genealogy of the strategy of 'resilience'. The paper notes that scholars writing critically about resilience tend to operate under the influence of Foucauldian method. It begins by asking to what degree genealogy forms the coherent method or set of methods in three Foucauldian analyses of resilience thinking. Identifying some questions for the literature in this context, the paper examines the place of strategies in Foucault's work, and how this relates to the genealogical method. Having suggested that genealogy must not ignore the history of strategies of confrontation, I illustrate my argument by looking at the role of resilience thinking in revolutionary strategy. This paper argues that lack of clarity about genealogy's key methodological principles has meant that reification is a recurrent problem in Foucauldian scholarship in this specific context, and has constrained study of the radical political potentialities of resilience.